Javanese-Mataraman Muslim Obedience towards Religious and State Leaders in Performing Friday Prayers during the COVID-19 Pandemic - Agus Machfud Fauzi; Novi Fitia Maliha; Mustofa Mustofa (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2021)
The Javanese-Mataraman Muslims have an ambiguous attitude in responding to government policies and religious leaders in carrying out Friday prayers during the early phase of COVID-19 pandemic, symbolically obeying not to do it. However, in reality, they still carry out Friday prayers. This article aims to find out the attitude of the community in making decisions on Friday prayers. They usually have an accommodative attitude in responding to the pros and cons of life problems. This article uses mixed methods with a snowball sampling technique to make it easier to find out the community’s attitudes using the dramaturgy approach since it had information about the informants’ front stage and backstage. The results of this study explain that they have obedience in the front stage. In contrast to the backstage, they perform Friday prayers even though the state and religion prohibit it. The dramaturgy is related to the religious understanding of the Javanese-Mataraman community, hampered by the rigid interpretation of the fiqh of worship, not to the knowledge of maqāṣid al-sharī‘ah.